Improvement of quality, physiological parameters and antioxidant status of chrysanthemum by priming of seedlings with UV-A radiation - Diego Iván ESCOBAR-HERNÁNDEZ; Yolanda GONZÁLEZ-GARCÍA; Emilio OLIVARES-SÁENZ; Adalberto BENAVIDES-MENDOZA; Antonio JUÁREZ-MALDONADO (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
In conventional chrysanthemum production systems, supplemental lighting is used to induce flowering. Plants perceive radiation in the range of 280 to 750 nm, and UV radiation has been shown to improve plant productivity. Modern technology allows efficient manipulation of these wavelengths, facilitating their direct application to seedlings. This study evaluated the effect of different UV-A exposure times (1, 2, 3 and 4 hours) on chrysanthemum seedlings of the varieties ‘Polaris’ and ‘Codorniz’ (Chrysanthemum × morifolium). In ‘Polaris’, priming the seedlings with UV-A increased growth by 8% and flower diameter by 6%, in addition to improving photosynthesis, with increases of up to 38%. The Fv/Fm index, an indicator of the photochemical efficiency of PSII, increased by 5%. In leaves, β-carotene increased by 45%, vitamin C by 8% and total chlorophylls by 56%. In petals, phenolics increased by 12% and 15%, while flavonoids increased by 12%. In contrast, ‘Codorniz’ showed less sensitivity to UV-A radiation, no change in growth and no change in biochemical compounds, although photosynthesis improved by 20%. UV-A radiation showed great potential for optimizing quality and productivity in chrysanthemums, especially in the ‘Polaris’ variety. These differences highlight the importance of taking into account the specific characteristics of each variety when implementing management strategies using UV-A light.